Identifying common factors of functioning, participation and environment amongst adults requiring specialist oral health care using the International Classification of Functioning, disability and health. - Alison Dougall; Francisca Martinez Pereira; Gustavo Molina; Caroline Eschevins; Blánaid Daly; Denise Faulks (PLoS ONE)
Introduction Persons unable to access oral health care in the conventional primary health care setting suffer from inequalities in oral health, particularly in terms of unmet dental need. The International Classification of Functioning, disability and health (ICF) is designed to look beyond medical diagnosis and to describe individuals or populations in terms of their ability to function and participate in a social environment. The objective of the study was to describe an adult population requiring specialist oral health care using the ICF and to identify common factors of functioning, participation and environmental context. Method The ICF Checklist for Oral Health was completed for 246 participants from five specialist dental services in five countries (mean age 36 ±16.44 years; 16-92). 'Developmental disability' and 'Medically compromised' groups were identified (72% and 28%). Results Participants presented with oral disease (92%) and dysfunction (66% impaired chewing). 33 ICF items were affected in over 50% of participants in both groups. Impaired body functions included 'ingestion functions', 'energy and drive functions' and 'emotional functions'. Participation was restricted for "Acquiring, keeping and terminating a job", "Intimate relationships", "Handling stress and psychological demands", "Economic self-sufficiency", "Carrying out a daily routine", "Recreation and leisure", "Community life" and "Looking after one's health". In the environment domain, "Support and relationships" and "Attitudes" were rated as facilitators. Environmental barriers reported for over 25% of the whole group were related to "Services, systems and policies" including, health, social security, general support, transportation, and labour and employment. Discussion and perspectives Common aspects of functioning, participation and environment were found amongst a heterogeneous population of adults attending specialist dental services, alongside poor oral health and function. The ICF may be used to describe populations that suffer inequality in oral health in order to develop services that effectively target those in need of additional means.